Performance Analysis and Comparison of Non-Inverting Buck-Boost Converter Using PI, OCC, and Hybrid OCC-PI Control - Ahmet Karaarslan; Ali Shaibu (Universitas Muhammadiyah Yogyakarta, 2022)
The study compares and analyses the performance of the one-cycle control (OCC), hybrid one-cycle-proportional integral control (OCC-PI), and the conventional PI control method applied to the non-inverting buck-boost converter. The hybrid OCC-PI control method combines the OCC and PI control techniques to provide a hybrid non-linear closed-loop control technique for regulating the buck-boost converter. The MATLAB/Simulink equivalent system model was simulated with design parameter variations using a wide input voltage range of 9 – 36 V, a nominal output voltage of 28 V, and a fixed switching frequency of 250 kHz to validate the control response speed, reliability, and robustness of the proposed control technique. The simulation results due to input voltage, output voltage, and load variations were carried out whiles recording the settling time, overshoots, efficiency, output voltage, and inductor current ripples due to each applied control technique. The simulation results indicated that the Hybrid OCC-PI control provides better response speed and a lower output voltage overshoot relative to the PI. It also provides better reference voltage tracking compared to the OCC control method.